Desarrollo de un software educativo como apoyo didáctico para los alumnos del segundo año de bachillerato técnico, del colegio técnico agropecuario Dr. Juan Francisco Ontaneda del cantón Chaguarpamba parroquia Buenavista en la elaboración de conserverías para uso doméstico y comercial utilizando materia prima de la zona en la asignatura de producción agropecuaria, período 2012-2013 - Armijos Carrión, Yobani Vicente (2014)
The made work serves as an educational support tool that helps in the teaching-learning process. Educational software is aimed at students of the Second Year of the technical hifh curriculo "Dr. Juan Francisco Ontaneda Agricultural Technical Highschool ", in order to provide interactivity with the pedagogical materials, achieving in this way meaningful learning. This Educational Software was realized specifically for students. Knowing the various activities required for the development of educational software, thisis based on the linking of computers to education. To fulfill goals we have set in the first instance we drawthe research project, building on a theoretical framework that served as reference model for the problem area. Furthermore, research has enriched us in very fundamental ways knowing the detailed level of processing. This software is a resource that could be used by a diverse audience, allowing cognitive flexibility. Finally, the help’s manuals were developed: the user manual which describes how to use it and Programmer's Manual which contains the schedule used inourmedia.